Impact of Ambient Music and Affability of Salespersons on Consumer Behavior in a Real Retail Setting with Emphasis on Gender Difference - Jha, Shalini; Singh, Bharti (Indian Journal of Marketing, 2013)
The Indian retail sector is facing intense competition. Though new stores and malls are coming up every day, but differentiating their retail offerings is a real challenge for all of them. It is difficult for retailers to maintain an advantageous position only from products, price, promotions and the retailing network. With the changing profile of the Indian customers, it is become very challenging for the retailers to allure the customers to their stores. By improving the in-store environment, a store can create an effective consuming condition to stimulate consumers’ immediate purchasing action. The present research paper is based on an experiment conducted in Big Bazaar, Bangalore. The experiment was conducted to find the interactive effect of two atmospheric cues - Music and Behaviour of the salespersons on consumer perception and buying behavior. The research is an attempt to understand the difference in behavior patterns due to the difference in gender with respect to the atmospheric stimuli selected for the study. The study shows that the effect of atmospheric stimuli - Music and Affability of the salespersons on perception, emotion and behavior remains the same for both the genders.